The Effect of Tax Knowledge, Awareness, Education and Financial Literacy on Individual Tax Compliance At Sawangan KPP - AGATHA, Thalia; WARDANI, Ni Made Sri (PT Keberlanjutan Strategis Indonesia, 2025)
Tax compliance is a crucial aspect in optimizing state revenue. However, the level of individual taxpayer compliance remains a challenge, particularly at the Depok Sawangan Primary Tax Service Office (KPP Pratama). This study aims to determine the influence of tax knowledge, tax awareness, education level, and financial literacy on the level of individual taxpayer tax compliance. This study used a quantitative approach with a survey method by distributing questionnaires to 100 respondents. Primary data were obtained from the questionnaire, while secondary data came from agency reports and available public sources. The data obtained were analyzed using multiple linear regression with the help of SPSS version 25 software. The results showed that only tax knowledge had a positive and significant effect on tax compliance, while the other three variables were insignificant. 5. Tax knowledge, tax awareness, education level, and financial literacy simultaneously had a significant effect on tax compliance. This indicates that the four variables together can explain variations in tax compliance.